Role of chemokine pathways in hepatobiliary cancer. Issue 2 (1st September 2016) - Ehling, Josef; Tacke, Frank
Highlights: Chemokines and their corresponding receptors regulate critical aspects in the pathogenesis of hepatobiliary cancer. Chemokines modulate the hepatic microenvironment toward an inflammatory, fibrotic, angiogenic and thus pre-neoplastic milieu. Liver neoplasms provoke pro- and anti-tumor immune responses regulated through differential activation of chemokine pathways. Malignant hepato-/cholangiocytes respond to distinct chemokine signals, which influence their proliferation and invasiveness. Pharmaceutical targeting of chemokine pathways is a promising approach to treat or even prevent hepatobiliary cancer. Abstract: Persistent hepatic inflammation resulting from hepatitis B or C virus infections (HBV or HCV, respectively), obesity-associated non-alcoholic steatohepatitis (NASH) or alcohol abuse is a hallmark feature of chronic liver diseases and appears to be an essential prerequisite of hepatocarcinogenesis. The inflammatory processes in the liver are regulated by various chemokines, which orchestrate the interaction between parenchymal liver cells, Kupffer cells (resident macrophages), hepatic stellate cells (HSC), endothelial cells, and infiltrating immune cells. In consequence, these cellular interactions result in the re-modeling of the hepatic microenvironment toward a pro-inflammatory, pro-fibrotic, pro-angiogenic and thus pre-neoplastic milieu. Once developed, liver neoplasms provoke pro- and anti-tumor immune responses that are also critically regulated through differential activation of chemokine pathways. With respect to hepatobiliary cancers, including hepatocellular carcinoma (HCC), gallbladder cancer and cholangiocellular carcinoma (cholangiocarcinoma), together belonging to the highest causes of cancer-related deaths worldwide, this review article will give an overview of chemokine pathways involved in both the establishment of a pro-tumorigenic microenvironment as well as the development and progression of hepatobiliary cancer. Pharmaceutical targeting of chemokine pathways is a promising approach to treat or even prevent hepatobiliary cancer.